Coupling stiffness-damping in modelling high-speed train track-embankment - Cunha, J. P. (2008)
The levels of demand associated with railways for high-speed trains imply great accuracy in the definition of numerical models for the prediction of its behaviour, Therefore, it is increasingly important to account for the nonlinear behaviour of foundation soils of these railways. These soils are subject to cyclic and dynamic loadings, and so, their dynamic response is highly affected by the induced level of cycling shear strain. Several studies have been done to characterize the stiffness and damping variation with cycling shear strain. In this study, this variation is formulated using the proposal of Ishibashi e Zhang (1993) and is used to study the influence of the cycling shear strain on soil foundations in the behavior of the high-speed tracks.